Analysis of leadership style, environment and work motivation on employee job satisfaction at PT PLN (Persero) UP3 North Medan: - - Haikal Dino Ramadhan; Samrin Samrin; Ikhah Malikhah (Junal Ilmu Manajemen, 2023)
This study aims to analyze the effect of leadership style, work environment, and work motivation on employee job satisfaction at PT PLN. Employee job satisfaction has an important role in achieving optimal performance and company success. Quantitative data analysis method used in this study. Data was collected through questionnaires distributed to employees of PT PLN. The variables studied include leadership style, work environment, work motivation, and employee job satisfaction. Statistical techniques, such as regression, are used to analyze the relationship between these variables. The results of this study indicate that participative leadership style, a supportive work environment, and high work motivation have a positive influence on employee job satisfaction at PT PLN (Persero) UP3 Medan Utara